Love and Knowledge: Emotion in Feminist Epistemology - Jaggar, Allison M. (Inquiry, 1989)
This paper argues that, by construing emotion as epistemologically subversive, the Western tradition has tended to obscure the vital role of emotion in the construction of knowledge. The paper begins with an account of emotion that stresses its active, voluntary, and socially constructed aspects, and indicates how emotion is involved in evaluation and observation. It then moves on to show how the myth of dispassionate investigation has functioned historically to undermine the epistemic authority of women as well as other social groups associated culturally with emotion. Finally, the paper sketches some ways in which the emotions of underclass groups, especially women, may contribute to the development of a critical social theory.
Keywords: discipline; genre; ressource en ligne; sciences humaines; théories féministes; émotions; épistémologie

Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes

The science question in feminism - Harding, Sandra G. (Cornell University Press, 1986)
Can science, steeped in Western, masculine, bourgeois endeavors, nevertheless be used for emancipatory ends? In this major contribution to the debate over the role gender plays in the scientific enterprise, Sandra Harding pursues that question, challenging the intellectual and social foundations of scientific thought.Harding provides the first comprehensive and critical survey of the feminist science critiques, and examines inquiries into the androcentricism that has endured since the birth of modern science. Harding critiques three epistemological approaches: feminist empiricism, which identifies only bad science as the problem; the feminist standpoint, which holds that women's social experience provides a unique starting point for discovering masculine bias in science; and feminist postmodernism, which disputes the most basic scientific assumptions. She points out the tensions among these stances and the inadequate concepts that inform their analyses, yet maintains that the critical discourse they foster is vital to the quest for a science informed by emancipatory morals and politics.
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis

Repères dans l’évolution d’une épistémologie féministe - Lasvergnas, Isabelle (Des femmes dans les sciences, 1986)
Un témoignage de quelques unes des formes des interrogations théoriques féministes telles qu'elles se sont structurées au cours des trente dernières années, et telles qu'elles prolifèrent désormais dans la polysémie — ainsi se présente ce numéro spécial des Cahiers de Recherche sociologique sur la thématique «Des femmes dans les sciences et des sciences sur les femmes».
Keywords: 1900-1999; EDI; approches et analyses; cours; discipline; discours dominant; fem1000; inégalités; premier cycle; périodes historiques; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie